Burnout dan Karakteristik Kepribadian pada Mahasiswa yang Bekerja Sambil Kuliah - Khairul Fatta; Sri Nurhayati Selian (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2026)
This study aims to analyze the phenomenon of burnout and the personality characteristics of students who work while studying. Students with dual roles are vulnerable to physical, emotional, and mental exhaustion due to simultaneous academic and work demands. This study used a qualitative approach with a case study design involving three Acehnese students as a single unit of analysis. Data were collected through in-depth interviews and analyzed using thematic analysis techniques. The results showed that the level of burnout experienced by students with dual roles was influenced by workload, time management, and social support. Furthermore, characteristics such as resilience, responsibility, and adaptability played an important role in determining the level of burnout experienced. Students with more resilient personalities tended to be able to manage stress better than those who were less able to adapt. This study is expected to provide an understanding of the importance of emphasizing management and personality development in facing the demands of dual roles among students.